Large-scale behavior-change initiative for infant and young child feeding advanced language and motor development in a cluster-randomized program evaluation in Bangladesh - Frongillo, Edward A.; Nguyen, Phuong Hong; Saha, Kuntal K.; Sanghvi, Tina; Afsana, Kaosar; Haque, Raisul; Baker, Jean; Ruel, Marie T.; Rawat, Rahul; Menon, Purnima (Elsevier, 2017)
Background Promoting adequate nutrition through interventions to improve infant and young child feeding (IYCF) has the potential to contribute to child development. Objective We examined whether an intensive intervention package that was aimed at improving IYCF at scale through the Alive & Thrive initiative in Bangladesh also advanced language and gross motor development, and whether advancements in language and gross motor development were explained through improved complementary feeding. Methods A cluster-randomized design compared 2 intervention packages: intensive interpersonal counseling on IYCF, mass media campaign, and community mobilization (intensive) compared with usual nutrition counseling and mass media campaign (nonintensive). Twenty subdistricts were randomly assigned to receive either the intensive or the nonintensive intervention. Household surveys were conducted at baseline (2010) and at endline (2014) in the same communities (n = ∼4000 children aged 0–47.9 mo for each round). Child development was measured by asking mothers if their child had reached each of multiple milestones, with some observed. Linear regression accounting for clustering was used to derive difference-in-differences (DID) impact estimates, and path analysis was used to examine developmental advancement through indicators of improved IYCF and other factors. Results The DID in language development between intensive and nonintensive groups was 1.05 milestones (P = 0.001) among children aged 6–23.9 mo and 0.76 milestones (P = 0.038) among children aged 24–47.9 mo. For gross motor development, the DID was 0.85 milestones (P = 0.035) among children aged 6–23.9 mo. The differences observed corresponded to age- and sex-adjusted effect sizes of 0.35 for language and 0.23 for gross motor development. Developmental advancement at 6–23.9 mo was partially explained through improved minimum dietary diversity and the consumption of iron-rich food. Conclusions Intensive IYCF intervention differentially advanced language and gross motor development, which was partially explained through improved complementary feeding. Measuring a diverse set of child outcomes, including functional outcomes such as child development, is important when evaluating integrated nutrition programs.